Consumer Comfort In The Café Industry: The Role Of Interior Design, Atmosphere, And Sensory Marketing - Ferry Hidayat; Billy Andrea; Iventura Fitra Uli Tamba (International Journal of Economics (IJEC), 2026)
This study aims to analyse the effect of interior design, café atmosphere, and sensory marketing on consumer comfort at KOA Café in Perdagangan, North Sumatra, Indonesia. This study uses a quantitative approach with associative methods. A total of 100 respondents were selected through purposive sampling techniques, and data were collected using questionnaire instruments related to interior design, café atmosphere, sensory marketing, and consumer comfort variables. Data analysis was conducted using multiple linear regression techniques. The results of partial analysis showed that interior design has a significant effect on consumer comfort with a value of tcount = 6.190 greater than Ttable = 1.986 and significance 0.000 (<0.05). Similarly, café atmosphere has a significant effect with a value of tcount = 2.564 greater than Ttable = 1.986 and significance 0.012 (<0.05). However, sensory marketing does not have a significant effect on consumer comfort with a value of tcount = 1.710 smaller than Ttable = 1.986 and significance 0.091 (>0.05). Simultaneously, interior design, café atmosphere, and sensory marketing significantly affect consumer comfort with a value of Fcount = 29.741 greater than Ftable = 2.704 and significance 0.000 (<0.05). The determination value of 46.6% indicates that the variables explain variations in consumer comfort. This study recommends that KOA Café management improve ergonomic interior design, maintain atmosphere consistency, and strengthen sensory marketing strategies to enhance consumer comfort and emotional attachment